URINARY INFECTION IN CHILDREN: PATHOGENETICAL DISORDERS AND THEIR CORRECTION FOR THE PROPHYLAXIS OF EXACERBATION - V.I. Kirillov; N.A. Bogdanova (Вопросы современной педиатрии, 2011)
Authors present the results of a study of pathogenetic mechanisms leading to the urinary tract infections in children with vesicoureteric reflux. Urine pH test with ammonium chloride detected decreasing of acidogenetic function of kidneys in children with urinary tract infection. Conventional antibacterial treatment of acute urinary tract infection combined with herbal medication Canephron N resulted in restoration of acidogenetic function of distal tubules and reducing of inflammation in urinary tract. Supportive treatment with herbal medication normalized urine flow with minimization of residual portion of urine. The treatment resulted in decrease of risk of recurrent urinary tract infections including pyelonephritic ones.Key words: children, urinary infections, vesico-ureter reflux, antibacterial treatment, Canephron N, treatment.(Voprosy sovremennoi pediatrii — Current Pediatrics. 2011; 10 (4): 100–104)